KELEKATAN ORANGTUA TERHADAP KEMAMPUAN KONTROL DIRI PADA REMAJA AWAL - Ardianti Agustin; Starry Kireida Kusnadi (Jurnal Psikologi Poseidon, 2019)
This study aims to determine the relationship between parental attachment, namely the attachment of the father and the attachment of the mother to the ability of self-control in early adolescence. The population of this study was early adolescents with an age range of 12-15 years as many as 104 adolescents. Samples were taken using the total sampling method for students of SMP 'X' in Surabaya. There are two scales in this study, namely: IPPA-R (Inventory of Parent and Peer Attachment-Revised) and SCS (Self-Control Scale). The data analysis technique used regression test with the help of SPPS 21. The results of this study indicate that there is a significant and positive relationship between parental attachment and self-control ability, which means that the higher the parental attachment, the higher the self-control ability. Father's attachment contributed 63.3% relative to self-control, while mother's attachment contributed36.7% relative to self-control where father's attachment had a greater influence on early adolescent self-control ability than attachment to mother.